1998
DOI: 10.1159/000015082
|View full text |Cite
|
Sign up to set email alerts
|

lntron based radiation hybrid mapping of 15 complex I genes of the human electron transport chain

Abstract: At least 34 complex I subunits of the electron transport chain are encoded by the nuclear genome, but only 14 of these have been mapped in the human. To rapidly map additional subunits, we have performed a combination of database mining and direct “wet” experimentation to identify intron and/or 5′ upstream genomic DNA regions for 16 complex I genes. Wet experimentation was applied to 5 genes, and involved direct PCR amplification of introns by inter-exon PCR or splinkerette based PCR walking. Database mining w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
(33 reference statements)
1
11
0
1
Order By: Relevance
“…Recently, we had certified that the NDUFS3, NDUFS8 and NDUFA10 protein expression levels were increased in the liver of broiler chickens after (-)-HCA supplementation [29]. NDUFS3 and NDUFA10 are important subunits of NADH dehydrogenase: NDUFS3 plays a vital role in the proper assembly of complex I [85], while NDUFA10 transfers electrons from NADH to ubiquinone in the respiratory chain [86]. Further, ATP synthase plays an important role in energy transduction, ATP synthesis catalyzed by ATP synthase is powered by the transmembrane electrochemical proton potential [87].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we had certified that the NDUFS3, NDUFS8 and NDUFA10 protein expression levels were increased in the liver of broiler chickens after (-)-HCA supplementation [29]. NDUFS3 and NDUFA10 are important subunits of NADH dehydrogenase: NDUFS3 plays a vital role in the proper assembly of complex I [85], while NDUFA10 transfers electrons from NADH to ubiquinone in the respiratory chain [86]. Further, ATP synthase plays an important role in energy transduction, ATP synthesis catalyzed by ATP synthase is powered by the transmembrane electrochemical proton potential [87].…”
Section: Discussionmentioning
confidence: 99%
“…Using cosmid ICRFc113D0635Q for FISH mapping we found a consistent signal on chromosome 7q31.3 (data not shown). This position has recently been confirmed by Emahasion et al (1998). We further refined the position of NDUFA5 by high-resolution mapping using two NDUFA5 specific STSs on the GeneBridge 4 Radiation Hybrid Panel (Research Genetics).…”
Section: Introductionmentioning
confidence: 55%
“…To confirm the positions of 5 Complex I genes we previously mapped by FISH (Dunbar et al, 1997), we performed intron based radiation hybrid (RH) mapping, employing at least one intron of each of the 5 genes. The intron based RH mapping strategy is described elsewhere (Emahazion et al, 1998). Our findings indicated that amongst the 5 previous FISH localisations, 4 were in error (NDUFA6, NDUFA7, NDUFB8, NDUFS8) while 1 was correct (NDUFA2).…”
Section: Rationale and Significancementioning
confidence: 65%
“…Intron based RH mapping of Complex I genes was undertaken as described elsewhere (Emahazion et al, 1998) using the Genebridge 4 Radiation Hybrid panel. PCR primers are detailed in Table 1.…”
Section: Methodsmentioning
confidence: 99%